2013
DOI: 10.1371/journal.pone.0061728
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Contrast Transfer Functions in Adults with and without ADHD

Abstract: In previous studies, we found a strong reduction in contrast perception and retinal contrast gain in patients with major depression, which normalized after remission of depression. We also identified a possible role of the dopaminergic system in this effect, because visual contrast perception depends on dopaminergic neurotransmission. Dopamine is also known to play an important role in the pathogenesis of attention deficit hyperactivity disorder (ADHD). Therefore, in order to explore the specificity of retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…Twenty unmedicated patients with ADHD (10 male and 10 female; 33.5±12.5 years of age) were identified at the ADHD program of the Department of Psychiatry and Psychotherapy of the University Hospital of Freiburg ( Table 1 ). The population is identical to the group of patients reported earlier with respect to PERG-based contrast gain [ 28 ].…”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…Twenty unmedicated patients with ADHD (10 male and 10 female; 33.5±12.5 years of age) were identified at the ADHD program of the Department of Psychiatry and Psychotherapy of the University Hospital of Freiburg ( Table 1 ). The population is identical to the group of patients reported earlier with respect to PERG-based contrast gain [ 28 ].…”
Section: Methodsmentioning
confidence: 79%
“…The background noise is markedly higher (138%) in patients with ADHD (red) compared to the controls (blue, p<0.005) and does not depend on stimulus contrast (lines are almost horizontal). This differs from the PERG stimulus response, which we added for comparison as dashed lines (data from [ 26 ]); the PERG response amplitude rises linearly with stimulus contrast.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to indirect effects on mood and anxiety via the impact of vision on function, the relationship may also include direct effects. Recent reports suggest that contrast sensitivity may be reduced in clinically depressed individuals, independent of any effect of mood on self-reported visual function (Bubl et al, 2013), and that even in the non-depressed, greater depressive symptoms are correlated with lower contrast sensitivity (Bubl et al, 2013). The authors further reported that contrast sensitivity normalizes with treatment of depression (Bubl et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, ocular proprioception is a major player in spatial localization and maintaining clear central eyesight [44,45], dovetailing with other research demonstrating that problems after brain injury can affect signaling in the peripheral retina. A recent study found evidence that retinal ganglion cells in the peripheral retina showed more activity in people with attention deficit disorder, as compared to a normal control group [46].…”
Section: Beyond the Retinamentioning
confidence: 97%